Peningkatan Daya Saing UMKM TahuLogi melalui Optimalisasi Media Promosi di Car Free Day Simpang Lima Gumul Kediri - Fadila, Putri Sari; Riawati, Popy; Rochimah, Pratiwi Zainur; Jingga, Pretty Dara; Reta, Putri Seifera Marga (Welfare : Jurnal Pengabdian Masyarakat, 2025)
MSMEs play an important role in the Indonesian economy, but many business actors still experience obstacles in marketing and branding their products. TahuLogi, an MSME in Kediri, faces challenges in increasing its competitiveness, especially in utilizing promotional media optimally. This community service activity aims to improve TahuLogi's marketing strategy through promotions at Car Free Day (CFD) Simpang Lima Gumul and the use of digital media. The methods used pengabdian ini kepada masyarakat menggunakan pendekatan Community-Based Research (CBR), include observation, digital marketing training, creating promotional materials, and evaluating the success of marketing strategies. The results of the activity showed an increase in TahuLogi's visibility and sales by 35%, as well as an increase in social media interaction by up to 40%. By optimizing offline and digital promotions, TahuLogi MSME now has a more effective and sustainable marketing strategy. This activity can be a model for other MSMEs in increasing their competitiveness in the digital era.